MOSSES AS BIOINDICATORS OF AIR POLLUTION ALONG AN URBAN–AGRICULTURAL TRANSECT IN THE CREDIT RIVER WATERSHED, SOUTHERN ONTARIO, CANADA - Cowden, P.; Liang, T.; Aherne, J. (Annali di Botanica, 2015)
The activities associated with urbanization, such as vehicular traffic and industrial processes, lead to elevated emissions of atmospheric pollutants. Measuring the spatial extent of these pollutants is pivotal to identifying areas of concern and assessing mitigation measures. The objective of this study was to evaluate the relative deposition of heavy metals and nitrogen using moss species along an urban–agricultural transition in the Credit River Watershed, southern Ontario. Thirteen species of moss were collected from Sugar Maple (Acer saccharum) dominated forest stands across the study area, with only one moss species (Atrichum altercristatum) commonly occurring. Heavy metal concentrations were variable between species; the Coefficient of Variation (CV) for the majority of metals (Al, V, Cr, Fe, Ni, As, Sb and Pb) was greater than ~50% across species. Nonetheless, metals exhibited similar trends, with the highest concentrations for Fe, followed by Al > Zn > Cu > Pb > Cr > Ni > V > As > Cd > Sb > Hg across species. Heavy metal concentrations in Atrichum altercristatum exhibited lower variability between sites, with CV < 33% for most metals (Cu, Zn, As, Cd, Sb, Pb and Hg). Further, many metal concentrations were strongly correlated (e.g., Al, V, Cr, Fe, and As; r ≤ 0.90) suggesting common emission sources, such as wind blown dust from agricultural activities or vehicular traffic, both predominant throughout the watershed.